当a^2+b^2=6,ab=-3时,求(2a-3b)(3a-2b)+(2a-b)^2+(2ab^2)^3÷8/3*a^3*b^4的值.

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/05 02:21:01
当a^2+b^2=6,ab=-3时,求(2a-3b)(3a-2b)+(2a-b)^2+(2ab^2)^3÷8/3*a^3*b^4的值.

当a^2+b^2=6,ab=-3时,求(2a-3b)(3a-2b)+(2a-b)^2+(2ab^2)^3÷8/3*a^3*b^4的值.
当a^2+b^2=6,ab=-3时,求(2a-3b)(3a-2b)+(2a-b)^2+(2ab^2)^3÷8/3*a^3*b^4的值.

当a^2+b^2=6,ab=-3时,求(2a-3b)(3a-2b)+(2a-b)^2+(2ab^2)^3÷8/3*a^3*b^4的值.
(2a-3b)(3a-2b)+(2a-b)^2+(2ab^2)^3÷8/3*a^3*b^4
=6a²-4ab-9ab+6b²+4a²+b²-4ab+3b²
=10a²-17ab+10b²
=10*6-17*(-3)
=60+51
=111